2018
DOI: 10.1094/mpmi-02-18-0050-r
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into the Nucleolar Localization of a Plant RNA Virus-Encoded Protein That Acts in Both RNA Packaging and RNA Silencing Suppression: Involvement of Importins Alpha and Relevance for Viral Infection

Abstract: Despite the fact that replication of plus-strand RNA viruses takes place in the cytoplasm of host cells, different proteins encoded by these infectious agents have been shown to localize in the nucleus, with high accumulation at the nucleolus. In most cases, the molecular determinants or biological significance of such subcellular localization remains elusive. Recently, we reported that protein p37 encoded by Pelargonium line pattern virus (family Tombusviridae) acts in both RNA packaging and RNA silencing sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 46 publications
1
19
0
Order By: Relevance
“…To explore which region(s) within MMDaV V2 is crucial for suppressing RNA silencing, we analyzed the MMDaV V2 sequence, and found that the RRLLRLIRRFSRVKDR motif between amino acid 61 and 76 defined a bipartite basic nuclear localization signal (NLS). Previous studies have indicated that the NLS of several VSRs is essential for the RNA silencing suppressor activity [ 31 , 37 , 38 , 39 ], prompting us to determine whether this motif is crucial for V2 to suppress PTGS. At a first step, we determined the subcellular localization of V2 via transient expression of eGFP-fused constructs into N. benthamiana leaves.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To explore which region(s) within MMDaV V2 is crucial for suppressing RNA silencing, we analyzed the MMDaV V2 sequence, and found that the RRLLRLIRRFSRVKDR motif between amino acid 61 and 76 defined a bipartite basic nuclear localization signal (NLS). Previous studies have indicated that the NLS of several VSRs is essential for the RNA silencing suppressor activity [ 31 , 37 , 38 , 39 ], prompting us to determine whether this motif is crucial for V2 to suppress PTGS. At a first step, we determined the subcellular localization of V2 via transient expression of eGFP-fused constructs into N. benthamiana leaves.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the fact that deletion of the putative NLS from MMDaV V2 did not prevent translocation of the protein into the plant nucleus, mutagenesis experiment demonstrated that the predicted basic motif of MMDaV V2 is indispensable not only for subnuclear foci localization but also for silencing suppression. In previous studies, nuclear import was found mandatory for several VSRs, such as βC1 of tomato yellow leaf curl China betasatellite and tomato leaf curl China betasatellite, P37 of Pelargonium line pattern virus, and P6 of cauliflower mosaic virus (CaMV) and strawberry vein banding virus, to suppress RNA silencing [ 31 , 37 , 38 , 39 , 54 ]. Nuclear import of CaMV P6 is conducted via two importin-α-dependent NLSs, and it is required for CaMV infection and suppression of the nuclear RNA silencing factor dsRNA-binding protein 4 (DRB4) [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, importin-αs also benefit pathogens, such as Pelargonium line pattern virus and Xanthomonas oryzae pv. oryzicola 9,10,49 .…”
Section: Discussionmentioning
confidence: 99%
“…Karyopherins including karyopherin-α (KPNA) and karyopherin-β (KPNB) is a nuclear transport receptor that is responsible for transporting its specific cargo proteins, which harbor nuclear localization signals (NLSs) through the nuclear pore complex (NPCs) (Beaudet et al 2020 ; Hazawa et al 2020 ). Some viruses, such as Japanese encephalitis virus (JEV) (Ye et al 2017 ), Ebola virus (EBOV) (Reid et al 2006 ), pelargonium line pattern virus (Perez-Canamas and Hernandez 2018 ), hantavirus (HTNV) (Taylor et al 2009 ), prevent nuclear import of cellular cargo molecules by binding importin family proteins or down-regulating importin alpha expression. Porcine reproductive and respiratory syndrome virus (PRRSV) induces KPNA1 degradation and inhibits ISGF3 Nucleation (Wang et al 2013 ).…”
Section: Discussionmentioning
confidence: 99%